PENGARUH INFLUENCER KEUANGAN DAN LITERASI KEUANGAN TERHADAP MINAT INVESTASI GENERASI MILENIAL DI PASAR MODAL - Tazkia, Aulia; Wijayanti , Risna (Jurnal Management Risiko dan Keuangan, 2022)
The high numbers of millennial investors in Indonesia have indicated the generation’s prospects to become potential investors for Indonesia’s future capital market development. However, as the financial literacy index of the country is still low, it is very likely that herding behavior appears among investors. Therefore, financial literacy is required to enable them to make rational investment decisions. The objective of this research is to identify the effects of financial influencer and financial literacy on the investment interest of millennials in the Special Capital Region of Jakarta. Here Partial Least Squares were used for the analysis, performed in SmartPLS 3.0. The samples are 100 individual investors categorized as millennials. This study finds that financial influencer and financial literacy positively and significantly determine individual interest on investment. Furthermore, financial literacy has a more dominant effect that financial influencer.